Arabic Teaching Studies: A Bibliometrics-Based Evaluation of Two Decade 2004-2024 - Yuniar Galuh Larasati; Henky Fernando; Novita Cahyani; Julia Magdalena Wusyang; Indah Kusuma Wardani (ALSINATUNA, 2024)
This study aims to explore and evaluate Arabic teaching studies published in the Scopus database in the last two decades 2004-2024. In addition to using bibliometric analysis-based methods, this study also uses VOSviewers-based software to explore and evaluate trends, patterns, and developments in Arabic teaching studies published in the Scopus database. This study found that trends, patterns, and developments in Arabic teaching studies published in the Scopus database have not comprehensively accommodated contemporary issues or problems in the last two decades 2004-2024, such as studies that focus on explaining the potential of internet-based technology as a potential Arabic language learning medium for teachers and students in improving their competence. This context can be used as a basis for evaluation in determining a new direction for the development of Arabic teaching studies in the future, amidst the massive transformation of internet-based technology.